REVIEW OF ISOLATION OF FUNGI FROM SHRIMPS - Badr, Sanaa Qasem (PT. Antis International Publisher, 2025)
Objective: This study aims to review the current knowledge on the isolation of fungi from shrimps, focusing on their ecological roles, pathogenic potential, and biotechnological applications. Method: A systematic review of previous studies was conducted, highlighting both direct isolation techniques, such as surface sterilization, agar plate, and dilution methods, and indirect approaches, including molecular identification and metagenomics. Results: The findings reveal a wide diversity of fungal genera, such as Aspergillus, Penicillium, Fusarium, Candida, and Cryptococcus, associated with shrimps, with implications for food safety, aquaculture health, and nutrient cycling in marine ecosystems. Several fungi were also identified as potential producers of bioactive compounds with antimicrobial and anticancer properties. Novelty: This review synthesizes traditional and modern approaches to fungal isolation in shrimp, bridging ecological insights with biotechnological potential, while emphasizing the urgent need for further research to address ecological risks and harness the benefits of marine-derived fungi in aquaculture and biotechnology.